2018
DOI: 10.1371/journal.pone.0208527
|View full text |Cite
|
Sign up to set email alerts
|

Implementation and maintenance of a pain management quality assurance program at intensive care units: 360 degree feedback of physicians, nurses and patients

Abstract: BackgroundPain management quality assurance programs (PMQP) have been successfully implemented in numerous hospitals across Europe. We aimed to evaluate the medium-term sustainability of a PMQP implemented at intensive care units (ICUs).MethodsTwo surveys, the first in 2012, immediately after introduction of the PMQP, and the second in 2015, were carried out amongst patients, physicians and nurses. Demographic parameters of all participants were assessed. Patients were asked after their pain levels during ICU … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…According to another study by Machira et al, the training and implementation of a pain management program had a positive impact on the knowledge and attitude of Kenyan nurses (26). The results of studies by Smolle et al at Austrian hospitals, which were conducted to assess the sustainability of a pain management quality assurance program (PMQP), showed that the implementation of PMQP led to a high standard of care, and continuous education, ongoing training, regular courses, and implementing feedback loops would ensure the continuity and the increase of knowledge and competency in nurses and physicians (29). However, a study by Schreiber et al in Kentucky, USA, to assess the impact of training interventions on the nurses' knowledge of pain management in critically ill patients, showed that the nurses' awareness scores were not significantly different before and after the intervention (24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to another study by Machira et al, the training and implementation of a pain management program had a positive impact on the knowledge and attitude of Kenyan nurses (26). The results of studies by Smolle et al at Austrian hospitals, which were conducted to assess the sustainability of a pain management quality assurance program (PMQP), showed that the implementation of PMQP led to a high standard of care, and continuous education, ongoing training, regular courses, and implementing feedback loops would ensure the continuity and the increase of knowledge and competency in nurses and physicians (29). However, a study by Schreiber et al in Kentucky, USA, to assess the impact of training interventions on the nurses' knowledge of pain management in critically ill patients, showed that the nurses' awareness scores were not significantly different before and after the intervention (24).…”
Section: Discussionmentioning
confidence: 99%
“…Training in intensive care units should encourage critical care nurses (CCNs) to understand and confidently use pain assessment tools ( 16 ). Continuous training on pain management, regular feedback sessions ( 29 ), and implementation of pain management programs can also have a positive impact on increasing the nurses’ knowledge and attitude ( 26 - 30 ). Additionally, pain control guidelines can increase the effectiveness of nurses' clinical practice ( 31 ), but it should be noted that a comprehensive pain management program should consider not only prevention, but also all the three phases of pain management including diagnosis, treatment, and reassessment of pain ( 7 ).…”
Section: Introductionmentioning
confidence: 99%